PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS PENDEKATAN KONSTRUKTIVISME UNTUK KELAS V SD - Sari, Rona Taula; Angreni, Siska; Fortuna, Retno Aulia (Universitas Sebelas Maret, 2019)
This study aims to describe the validity and practicality of science learning modules based on the constructivism approach to the material adaptation of plants to certain environments to sustain life in valid and practical class V elementary school students. This type of research is Research and Development. The science learning module based on the constructivism approach was developed using 3-D models. This research was conducted in the even semester of the 2018/2019 school year. Data collection is done by validation and testing of modules developed. The module design that was designed was validated by two expert lecturers and then tested in class V of SD Negeri 07 Lubuk Jantan to find out the practicality and validity of the modules developed. The results of the study found that the science learning module based on the constructivism approach on the material adaptation of plants to certain environments to sustain life for students in grade V elementary school is in the category of very valid with an average validity of 3.65. The modules that have been developed are categorized as very practical by educators with an average percentage of practicality of 91%, also categorized as very practical according to students with an average percentage of practicality of 91%. This shows that the science learning module is based on a constructivism approach to the material adaptation of plants to certain environments to maintain the life produced is very valid and very practical so that it can be used in learning in class V SD.